Validation of blue- and clear-native polyacrylamide gel electrophoresis protocols to characterize mitochondrial oxidative phosphorylation complexes - Jana Aref; Seungtae Lee; Supachaya Sriphoosanaphan; Micol Falabella; Shi-Yu Yang; Jan-Willem Taanman (PLoS ONE, 2025)
The mitochondrial oxidative phosphorylation (OXPHOS) system plays a pivotal role in the cell’s energy conversion. The enzymes involved in OXPHOS are arranged in five protein-lipid complexes. The first four complexes (I–IV) form the mitochondrial respiratory chain, while Complex V is an F1Fo-ATP synthase. Mutations in genes involved in the biosynthesis of the OXPHOS complexes are an important cause of metabolic diseases. Blue-native polyacrylamide gel electrophoresis (BN-PAGE), originally developed by Hermann Schägger in the 1990s, has become instrumental in gaining insights into structure/function relationships of the OXPHOS system, including: (1) the assembly pathways of the complexes, (2) the composition of higher-order respiratory chain supercomplexes and (3) pathologic mechanisms in patients with a monogenetic OXPHOS disorder. We have used BN-PAGE for >20 years and validate here our recently published step-by-step laboratory protocol. This protocol describes the manual casting of native mini-gels and sample preparation for the resolution of individual OXPHOS complexes or respiratory chain supercomplexes. In addition to BN-PAGE, we explain the closely related clear-native (CN)-PAGE and two-dimensional BN/denaturing-PAGE techniques. Downstream applications include western blot analysis and in-gel enzyme activity staining for Complexes I, II, IV and V. Limitations of the technique are the comparative insensitivity of in-gel Complex IV activity staining and the lack of in-gel Complex III activity staining. Compared to other published BN-PAGE protocols, our protocol contains a shortened sample extraction procedure, advises when to use BN-PAGE and when to use CN-PAGE, and suggests a simple enhancement step for in-gel Complex V activity staining that markedly improves sensitivity. Our protocol is adaptable and yields robust, semi-quantitative and reproducible results.